Predicting lesion complexity in premature coronary artery disease: The utility of clinical risk scores - Firdaus, Achmad Jauhar; Mohammad Saifur Rohman; Budi Satrijo; Cholid Tri Tjahjono; Anna Fuji Rahimah (Heart Science Journal, 2025)
Background: Premature coronary artery disease (PCAD) has been recognized as a significant global health issue, with its prevalence increasing due to earlier exposure to various risk factors. Emerging evidence suggests that PCAD may be as aggressive, if not more so, than in older populations. The clinical implications and angiographic characteristics for more aggressive management strategies remain poorly explored. Objectives: This study aims to develop and validate a clinical scoring system in predicting lesion complexity in patients with PCAD. Methods: A retrospective cohort study was conducted on 645 patients who underwent invasive coronary angiography (ICA) from January 2023 to December 2024 in Dr. Saiful Anwar General Hospital, East Java, Indonesia. Patients were divided into developmental (n = 322) and validation (n = 323) groups. Clinical information was gathered from medical records, including risk factors and angiographic results. Predictors of complex CAD (SYNTAX ≥ 33) were identified by multiple logistic regression analysis. A clinical scoring system was developed and validated. Results: This study found complex CAD in 252 (39.1%) of all PCAD patients. Smoking (OR 2.3; p 0.006), dyslipidemia (OR 2.8; p < 0.001), diabetes mellitus (OR 3.9; p < 0.001), history of previous myocardial infarction (OR 6.5; p < 0.001), and family history of CAD (OR 5.7; p < 0.001) were independent predictors of complex CAD. A clinical scoring system was developed with a cut-off score ≥ 4 predicting complex CAD, with an area under the curve (AUC) value of 0.836 (95% CI 0.791-0.880), sensitivity of 71.3%, and specificity of 85.0%. Conclusion: The PCAD population continues to represent a high-risk group of concern. While the short-term prognosis is optimistic, the long-term outlook for this cohort is less promising due to the high recurrence rate and prolonged complications, especially in individuals with complicated CAD, leading to impaired quality of life